Atributos físicos de um latossolo cultivado com cana-de-açúcar após aplicações de lodo de esgoto e vinhaça - Camilotti, Fábio [UNESP]; Andrioli, Itamar [UNESP]; Marques, Marcos O. [UNESP]; Silva, Alysson R. da [UNESP]; Tasso Júnior, Luiz C. [UNESP]; Nobile, Fabio O. de [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2006)
O objetivo deste trabalho foi avaliar se a aplicação anual de lodo de esgoto e vinhaça, resíduos empregados com a finalidade exclusiva de fornecer a quantidade necessária de N e K para cana-de-açúcar, causaria alteração em alguns atributos físicos de um Latossolo Vermelho distroférrico argiloso, após as colheitas do 3º e 4º cortes da cultura. O experimento foi conduzido em blocos ao acaso, com três repetições. Os tratamentos foram: (i) dose de lodo de esgoto para suprir 100% do N exigido pela cultura; (ii) dose de lodo de esgoto para suprir 200% do N exigido; (iii) dose de vinhaça para suprir 100% do K exigido; (iv) dose de vinhaça para suprir 200% do K exigido; (v) combinação dos tratamentos (i) e (iii); (vi) combinação dos tratamentos (ii) e (iv); (vii) testemunha (adubação mineral recomendada). Os somatórios das doses dos resíduos foram de 39 e 51 t ha-1 de lodo de esgoto e de 870 e 1.174 m³ ha-1 de vinhaça até o 3º e 4º cortes, respectivamente. Nas camadas de 0-10; 10-20; 20-30; 30-40 e 40-50 cm de profundidade, após as colheitas do 3º e 4º cortes da cultura, foram determinados: teor de matéria orgânica, porosidade total, macroporosidade, microporosidade, densidade do solo, densidade de partícula, resistência do solo à penetração e teor de água gravimétrico. Aplicações de lodo de esgoto e vinhaça não causaram modificação nos atributos físicos, resultado associado à falta de efeito dos resíduos na matéria orgânica do solo.

The objective of this work was to evaluate if annual application of sewage sludge and vinasse, residues employed with exclusive purpose of supply N and K to sugar cane, would cause alteration on some physical attributes of clayey Haplustox after the harvests of the 3rd and 4th cuts of the crop. The experiment was carried out in a complete randomized block design with three repetitions. The treatments were: (i) rate of sewage sludge to supply 100% of the required N by the crop; (ii) dose rate of sewage sludge to supply 200% of the required N; (iii) rate of vinasse to supply 100% of the required K; (iv) rate of vinasse to supply 200% of the required K; (v) combination of the treatments (i) and (iii); (vi) combination of the treatments (ii) e (iv); (vii) control (mineral fertilization recommended). Sums rates of the residues were of 39 and 51 t ha-1 of sewage sludge and 870 and 1,174 m³ ha-1 of vinasse until the 3rd and 4th cuts, respectively. Soil samples were taken in the layers of 0-10, 10-20, 20-30, 30-40 e 40-50 cm of depth, after the harvests of the 3rd and 4th cuts of the crop. In these samples were determined the organic matter content, total porosity, macroporosity, microporosity, soil bulk density, particle density, soil resistance to penetration and gravimetric water content. Sewage sludge and vinasse applications did not cause any alteration on the physical attributes, result associated to lack of effect of the residues in the soil organic matter.
Physical atributes of oxisol cultivated with sugar cane after applications of sewage sludge and vinasse
Keywords: Organic residue; Saccharum; soil organic matter; Matéria orgânica do solo; Residuos organicos; Saccharum